M238. CREATION OF A PEER SUPPORT PROGRAM TO SUPPORT TRANSITIONS IN CARE FROM EARLY INTERVENTION SERVICES FOR PSYCHOSIS. (18th May 2020) - Crocker, Candice; Cox, Andy; Abidi, Sabina; Ursuliak, Zenovia; Epstein, Noah; Hughes, Jean; Crown, Margie; Tibbo, Philip
Abstract: Background: Specialized early intervention services (EIS) for psychosis have been shown to have superior outcomes compared to routine care. However, these gains are often lost when care is transferred to community mental health care teams. Research has shown that young adults experience anxiety, worry and stigma around the transition process from EIS, which can impact ongoing engagement with treatment. Transition to a new care team has been shown to be a time for disengagement. Despite this area's acknowledged importance, there is a paucity of literature on how to maintain engagement during the transition process from an EIS to community services. We conducted a qualitative study with EIS for psychosis patients in various phases of transition which informed the development of a peer support program focused on the transition time period. Methods: Focus groups were conducted to identify strengths and weaknesses of the transition process from a Canadian EIS program. Thematic analysis was conducted on the transcripts from the focus groups. Following themes from the focus groups, a research study was developed to create and evaluate a peer support worker (PSW) program for individuals in transition from the EIS. Peer support workers were recruited from individuals who had successfully transitioned from the same five year EIS for psychosis program. Individuals underwent training as peer support workers that was tailored to the needs of individuals with a psychotic disorder. Peer support workers met with clients in both clinical and community settings with support and feedback provided by clinicians in the EIS. Results: Strengths identified included preparation time, helping individuals feel stable prior to transition and inclusion in decision making. Weaknesses included communication, more individualized preparation for transition and a desire for more opportunities to build independence and responsibility. A major theme was lack of peer support during the process, with a voiced desire to maintain connection to EIS by being a peer mentor in those who had already transitioned out. We recruited 7 individuals interested in becoming PSW and with a PSACC Certified Peer Support Mentor, designed a curriculum for training based on his peer support training experience with feedback from clinicians to customize it to the experience of living with psychosis and transition. The features of this curriculum will be discussed. 5 of 7 individuals completed training. 4 expressed an interest in being hired. 1 was not able to complete the hiring process but did an exit interview and impediments to hiring included costs associated with hiring practices that needed to be paid up front then reimbursed, limited internet access to a secure connection that allowed HR software to function and transportation issues. 3 individuals were hired as PSW (2 F, 1M) and supported participants transitioning from our clinic who were interested. PSW would meet in the clinic with individuals prior to transition then support them in the community for several months after transition. 1 PSW relapsed during the course of the study. Only 1 PSW has continued with our program. Patients in transition participating in the program underwent semi-structured interviews that indicated satisfaction with the program. Discussion: At project launch, we examined the literature and could only find one paper related to the concept of PSW and transition in psychosis. Having lived the process of developing the program, we gained an understanding of the difficulties of enacting what we have found to be a highly successful adjunct to our program. PSW programs involving individuals with psychosis are expensive to launch and attrition is high but these costs need to be weighed against improved transition outcomes.